The Impact of Innovation Strategy on Organizational Success: A Study of Samsung - Binti Mohd Haizar, Nor Fitrah; Kee, Daisy Mui Hung; Chong, Lai Mei; Chong, Jing Han (Asia Pacific Journal of Management and Education (APJME), 2020)
The purpose of this study is to examine the impact of Samsung’s innovative strategy on organizational success. Today, the smartphone market has been fast evolving and it becomes a necessity to mankind. Samsung, one of the giant players which dominates the global smartphone market, has carried out innovative strategies, such as releasing smartphones with new features that cater the needs of customers, and achieves higher sales compared to its competitors in the smartphone market. This study emphasizes the innovative strategies that lead to Samsung's success. Besides, this study also looks at Samsung's opportunity and creativity to gain smartphones innovative leadership based on the 5G emerging technology. The finding of this study indicates that innovative strategy is positively related to the success of the organization.